Bottled water- problem in campus - Chandwani, Rajesh, (SAGE Business. Cases., 2019)
The case is based on heated email conversations regarding the delivery of clean bottled water in the campus of a reputed research Institute, Arumalai Research Institute, in Southern India. The conversations were between Tara Sharma (Programme Manager - Executive Programme Division) and Shreejith Nair (Head-Engineering, Service & Estate). The case presents the viewpoints of various stakeholders involved in the open conversation.